The Effect of Population Density on the Water Quality of the Deli River in Medan - Harahap, Dakwan Soaloon (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Medan City is one of the largest cities in Indonesia in terms of population. Unfortunately, the high population density in Medan City has the potential to cause several negative impacts, including on environmental sustainability. One of the rivers in Medan City is the Deli River. Therefore, the aim of this research is finding out the effect of population density on the quality of river water in Deli River, Medan City compared to the Tembung River, Deli Serdang Regency, which is more sparsely populated. Data collection was carried out by testing the quality of both rivers water samples. It is known that the water quality of the Tembung River which is located in Deli Serdang Regency has better quality compared to the water quality of the Deli River in Medan City. Tembung River water has test results: 1) pH value of 8.0; 2) slightly pungent odor; 3) slightly yellowish clear color; while the Deli River water test results: 1) pH value 7.6; 2) very strong odor; 3) blackish yellow color. It can be concluded that the denser the population in an area has the potential for lower river water quality in that area.